Phase Equilibrium and Crystallization Process of the Ternary System KCl-(NH2)2CO-H2O at Different Temperatures - Liqiong Chen; Tianxiang Li; Lianjun Shi; Shihan Wang; Zeyu Meng; Jie Zhang; Jing Zhu (Journal of Chemistry)
The phase equilibriums of the ternary system KCl-(NH2)2CO-H2O at 303.15 K, 323.15 K, 333.15 K, and 343.15 K were studied using the isothermal dissolution equilibrium method, in which the composition of equilibrium solid phase was determined by Schreinemaker’s wet residue method and X-ray diffraction (XRD) method. It was found that the ternary system is a simple cosaturated system, without the formation of neither double salt nor solid solution. Wilson and NRTL models were employed to correlate in the solubility data of the system at experimental temperatures. The maximum values of RAD and RMSD of the Wilson model were 2.18 × 10−2 and 0.83 and those of the NRTL model were 1.69 × 10−2 and 0.40, respectively. The two models were utilized to forecast solubility data at various temperatures, and the obtained outcomes were in line with the literature data. Based on the experimental solubility data at 343.15 K, the cooling crystallization process of the system was monitored online by focused beam reflectance measurement (FBRM) and particle video microscope (PVM). The crystal products were characterized by XRD, scanning electron microscope (SEM), and energy dispersive spectrometry (EDS). The results showed that the precipitation of (NH2)2CO occurred during the crystallization process, and this was followed by KCl. KCl was formed on the surface of (NH2)2CO crystal. The crystal was a simple mixture containing KCl and (NH2)2CO.